Heart rate variability and mild cognitive impairment in parkinson’s disease - Merello, Marcelo (2020)
Fil: Merello, Marcelo. Fleni. Instituto Raúl Carrea de Investigaciones Neurológicas, Movimiento Unidad de Trastornos; Argentina